(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article provides a comprehensive analysis of women writers in English literature, examining their historical context, themes explored, notable authors and their works, challenges faced, and the enduring influence they have had on the literary landscape.